Application of Virtual Reality Combined with Eye Tracking Technology for Design Flows - Yan, Wang; Vongphantuset, Jirawat (2020 International Conference on Big Data and Informatization Education (ICBDIE), 2020)
In this paper, a combination of virtual reality (VR) and eye tracking technology applied in design process is presented. The efficacy evaluation of the proposed application is further discussed. The paper combines the ARCS and IMMS models. Furthermore, traditional design process is researched and optimized, which not only helps to enhance the design efficacy, but is also suitable for improving the efficiency of the whole industry. This interdisciplinary research provides theoretical and technical bases for the application and evaluation of immersive design in different disciplines, showing high academic and practical significance.